Regulation of immunoglobulin diversification pathways by AID in a transgenic mouse model. - Shansab, Maryam. (2017)
Abstract: The activation-induced cytidine deaminase (AID) enzyme plays a central role in B-cell diversification such as somatic hypermutation (SHM), immunoglobulin (Ig) V-gene conversion, and class switch recombination (CSR). AID function has also been implicated in chromosomal B-cell translocations between the c-myc oncogene and the immunoglobulin heavy-chain (Igh) locus. The regulatory mechanisms that promote such vastly different outcomes after AID deamination are not clear. To better understand AID-dependent pathways, I have used a transgenic mouse, which carries an antibody (Ab) heavy chain transgene, to monitor CSR, SHM, and Ig V-gene conversion. I have shown that Igh/transgene translocations require AID and resemble interchromosomal CSR events, although the recombination mechanism does not appear to involve trans-switching between the transgene Smu region and the endogenous Smu region. Because trans-switching between the same S regions would not generate a change in Ab class, these results suggest that CSR may be regulated to maximize B-cell responses to antigens. My results also show that, although Ig V-gene conversion is not detected at the transgene locus, the transgene is capable of accumulating AID-induced mutations, which are dependent on the function of the Base Excision Repair (BER) and Mismatch Repair (MMR) pathways. These results indicate that Igh cis elements 5' of the Cmu gene are sufficient to promote the mutagenic function of BER and MMR, and that missing cis elements downstream of the Cmu gene probably function to recruit AID to Ig loci more efficiently, which in turn may be needed for gene conversion. Furthermore, because double stranded DNA breaks (DSBs) may be needed for Ig V-gene conversion, these results imply that the extent of DNA damage may dictate how the damage is resolved. Finally, I show that p21 is dispensable for SHM and CSR. Together, my results indicate that one of the functions of the Ig regulatory elements may be to make AID deamination more efficient, which in turn, may determine how AID-induced DNA damage is resolved.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Immunology.; Advisors: Erik Selsing, and Naomi Rosenberg.; Committee: Peter Brodeur, and Henry Wortis.; Keyword: Immunology.